France : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2012)
This Financial System Stability Assessment on France discusses the French financial system and the restructuring of French banks to different business models. The French banking system weathered the 2007-09 global financial crisis well. The large French banks have announced plans to meet Basel III Common Equity Tier 1 (CET1) capital targets during 2013, and have divested noncore assets. The banks are increasing their liquidity and reducing their dependence on short-term and U.S. dollar wholesale funding. IMF staff recommends timely feedback and strengthened follow-up mechanisms in the supervisory process.